The 23-year tracking of blood lipids from adolescence to adulthood in Korea: the Kangwha study - Lee, Jung Hyun (Lipids Health Dis, 2017)
BACKGROUND: Several studies have examined tracking pattern of blood lipids level during long follow-up periods in Western countries. However, there have been few such studies in Asian populations. METHODS: The Kangwha Study is a community-based prospective cohort study that started in 1986 on Kangwha Island, South Korea. A total of 432 participants (47% men) were enrolled in the study, during which serum total cholesterol, triglycerides, and high-density lipoprotein (HDL) cholesterol levels were measured for each participant at least once during adolescence (12–16 years of age) and again at least once during adulthood (25–35 years of age). The tracking patterns of the blood lipid levels were determined using Spearman correlation coefficients and tracking coefficients from generalized estimating equations. RESULTS: The Spearman correlation coefficients between lipid measurements ranged from 0.12 to 0.73 depending on the lipid profile and measurement time interval; all were significant (p < 0.05). The magnitude of the coefficients tended to decrease as the time interval increased. When adjusted for age, sex, body mass index, and blood pressure, the tracking coefficients were 0.58 (95% confidence interval [CI]: 0.54–0.63) for total cholesterol, 0.39 (95% CI: 0.31–0.48) for triglycerides, and 0.51 (95% CI: 0.47–0.56) for HDL cholesterol. In a subgroup analysis by sex, the tracking coefficients were higher for women than for men, except for HDL cholesterol. CONCLUSIONS: The tracking patterns of blood lipids from adolescence to adulthood were notable. This study supports the importance of measuring lipids during adolescence for identifying high-risk individuals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12944-017-0615-2) contains supplementary material, which is available to authorized users.